Electron impact excitation of Al XIII: Collision strengths and rate coefficients - Aggarwal,KM; Keenan,FP; Rose,SJ (2001)
Collision strengths for transitions among the n = 5 levels of Al XIII have been computed in the LS coupling scheme using the R-matrix code. All partial waves with angular momentum L ≤ 45 have been included, and resonances have been resolved in a fine energy grid in the threshold region. Collision strengths have been computed at energies below 220.0 Ryd, and effective collision strengths, obtained after integrating the collision strengths over a Maxwellian distribution of electron velocities, are calculated over a wide temperature range of 4.40 ≤ log Te ≤ 6.0 K.